THE EFFECT OF TYPE AND COMPOSITION OF PLASTICIZER ON THE CHARACTERISTICS OF POLYSULFONE (PSF) MEMBRANES - Oktaviana Trisna Dewi, Aptika
The use of synthetic plasticizers especially phthalic compounds as additives in polymer or membrane materials can cause carcinogenic effect for human beings. This study aims to find an alternative natural plasticizer that has no such negative effect. Two types of polysulfone (PSf) membranes were made by a phase inversion method using different plasticizers namely, dioctyl phthalate (DOP) and soybean oil (SBO). N-methyl-2-pyrrolidone (NMP) was used as a solvent for PSf- DOP, while dimethyl acetamide (DMAc) for PSf-SBO. PEG 400 was added as pore forming agent and water was used as a coagulant. Composition of plasticizer was varied between 0 to 5% w/w. The membrane characteristics was evaluated in terms of water flux, rejection (%R) of 500 kDa and 2000 kDa dextran solutions, contact angle, mechanical properties and morphology structure. The water flux of the PSf-DOP membranes under the trans membrane pressure of 1.5 atm was shown to be higher than the PSf-SBO membranes due to the hydrophobic characteristic of SBO. In fact, the contact angle of the PSf-DOP was smaller than that of PSf-DOP. When the SBO concentration was increased, the water flux decreased and the rejection increased for the 2000 kDa dextran solution. The hydrophobicity of SBO can slowed up the diffusion rate of the non-solvent to the polymer solution, resulting in narrower finger-like structure and higher elasticity in the PSf-SBO than the PSf-DOP membranes. It is concluded that the SBO can be used as a plasticizer for PSf membranes. It acts as a lubricant which slipped among polysulfone chains resulting in more elastic membranes.